2012
DOI: 10.3161/000164512x653917
|View full text |Cite
|
Sign up to set email alerts
|

Major Roads Have a Negative Impact on the Tawny OwlStrix alucoand the Little OwlAthene noctuaPopulations

Abstract: Abstract. The increasing road networks threaten ecosystems by direct effects such as increased mortality due to collision with vehicles and by various indirect effects leading to road avoidance. We censused Tawny Owls Strix aluco and Little Owls Athene noctua in 2005, 2007 and 2009 in a rural landscape in Southern Portugal in order to study the effects of roads and habitat characteristics on Tawny Owl density and Little Owl presence. The presence of both owl species in the 70 census locations was coherent amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 37 publications
1
36
0
Order By: Relevance
“…Nevertheless, only three of these studies determined the extent of the road-effect zone [56][57][58]. This low number was surprising considering the increasing popularity of tools, such a simulation models (see Consequences of Road Networks on Wildlife Populations section below) that are used to explore the impact of road networks on wildlife populations.…”
Section: Indirect Impacts Of Roads On Wildlifementioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, only three of these studies determined the extent of the road-effect zone [56][57][58]. This low number was surprising considering the increasing popularity of tools, such a simulation models (see Consequences of Road Networks on Wildlife Populations section below) that are used to explore the impact of road networks on wildlife populations.…”
Section: Indirect Impacts Of Roads On Wildlifementioning
confidence: 99%
“…The accuracy of such models depends on the inclusion of the roadeffect zone as it is a more realistic representation of the potential habitat loss associated with roads. For example, a study on Tawny owls (Strix aluco) in rural Portugal found that owl density could be impacted up to 2 km from a major road [56]. Even for a common and widespread species such an impact has the potential to influence population numbers and persistence in the area.…”
Section: Indirect Impacts Of Roads On Wildlifementioning
confidence: 99%
“…These studies on Spotted Owls applied temporary noise stimuli, e.g., helicopters, chainsaws, or motorcycles, so it is not known how owls respond to a permanent noise source on the landscape. Increased proximity to roads and increased traffic volume has been found to decrease owl density and occupancy of sites (Hindmarch et al 2012, Silva et al 2012, which may be at least partially due to the masking effect of traffic noise. However, roads have several factors other than noise (vehicle collisions, pollution, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…The development of road networks and increased traffic volume is one the most significant causes of habitat fragmentation (Forman and Alexander, 1998;Trombulak and Frissell, 2000;Forman et al, 2003;Fahrig and Rytwinski, 2009;Selva et al, 2011) that has lead to decreased populations of many animal species (Warren et al, 2001;Fahrig, 2003;Forman et al, 2003;Thomas et al, 2004;Biesmeijer et al, 2006;Silva et al, 2012). Several studies, mostly carried out on mammals, amphibians and some insects, indicate that roads dividing habitat fragments may be an obstacle to the movements of individuals and, therefore, to the gene flow between the fragments (Bhattacharya et al, 2003;Shepard et al, 2008;Smith-Patten and Patten, 2008;Jackson and Fahrig, 2011;Soluk et al, 2011;Neumann et al, 2012).…”
Section: Introductionmentioning
confidence: 99%